Gemcitabine-mediated depletion of immunosuppressive dendritic cells enhances the efficacy of therapeutic vaccination - Repáraz, David; Ruiz, Marta; Silva, Leyre; Aparicio, Belén; Egea, Josune; Guruceaga, Elizabeth; Ajona, Daniel; Senent, Yaiza; Conde, Enrique; Navarro, Flor; Barace, Sergio; Alignani, Diego; et al. (Frontiers in Immunology, 2022)
Vaccination using optimized strategies may increase response rates to immune checkpoint inhibitors (ICI) in some tumors. To enhance vaccine potency and improve thus responses to ICI, we analyzed the gene expression profile of an immunosuppressive dendritic cell (DC) population induced during vaccination, with the goal of identifying druggable inhibitory mechanisms. RNAseq studies revealed targetable genes, but their inhibition did not result in improved vaccines. However, we proved that immunosuppressive DC had a monocytic origin. Thus, monocyte depletion by gemcitabine administration reduced the generation of these DC and increased vaccine-induced immunity, which rejected about 20% of LLC-OVA and B16-OVA tumors, which are non-responders to anti-PD-1. This improved efficacy was associated with higher tumor T-cell infiltration and overexpression of PD-1/PD-L1. Therefore, the combination of vaccine + gemcitabine with anti-PD-1 was superior to anti-PD-1 monotherapy in both models. B16-OVA tumors benefited from a synergistic effect, reaching 75% of tumor rejection, but higher levels of exhausted T-cells in LLC-OVA tumors co-expressing PD-1, LAG3 and TIM3 precluded similar levels of efficacy. Our results indicate that gemcitabine is a suitable combination therapy with vaccines aimed at enhancing PD-1 therapies by targeting vaccine-induced immunosuppressive DC.